Unfavorable low-risk factors predict pathologic upstaging and upgrading following radical prostatectomy: Evidence for further subclassification of low-risk prostate cancer? - Magdelinić Aleksandar; Spasić Aleksandar; Vuković Marko (Srpski Arhiv za Celokupno Lekarstvo, 2025)
Introduction/Objective. We aimed to validate the stratification of low-risk prostate cancer (PCa) into “favorable” and “unfavorable” subgroups of patients undergoing radical prostatectomy (RP), based on the correlation of various biopsy features with high-risk characteristics at final pathology. Methods. The research involved 173 patients who were selected as low-risk PCa. The planned stratification categorized patients into favorable and unfavorable low-risk PCa subgroups, based on their Gleason upgrading (GU) and tumor upstaging (TU) status at final pathology. Unfavorable low-risk PCa was defined by the presence of biopsy results correlating with high-risk characteristics at final pathology, pathological Gleason score (pGS ≥ 4 + 3, or ≥ pT3a, or pN1). Patients were divided into two groups according to the presence of high-risk pathology features: Group 1 (n = 84, favorable) and Group 2 (n = 89, unfavorable). Results. In total, 18 patients from the second group (20.2%) experienced Gleason score upgrading (GS ≥ 4 + 3), and in 94.4% of these cases, their biopsy reports indicated the presence of both perineural invasion (PNI) and lymphovascular invasion (LVI). Furthermore, among patients with upstaging to pT3a or pT3b, both PNI and LVI were observed in 60% and 85.7% of cases, respectively. Multivariate analysis demonstrated that PNI (OR = 3.35; 95% CI: 1.16–7.56; p < 0.001) and LVI (OR = 5.34; 95% CI: 2.02–11.2; p < 0.001) were independently associated with both GU and TU. Conclusion. The presence of PNI and LVI in prostate biopsy samples is associated with both clinically significant GU score and TU following pathologic prostate examination. Therefore, these features represent unfavorable characteristics in biopsy results.